Fault lines in the graveyard: The contested nature of green burial. Issue 4 (5th December 2018) - Stewart, Benjamin M.
Abstract: The natural burial movement is popularly portrayed as the reemergence of simpler death practices and spiritualities. Without denying its ecological simplicity and ritual honesty, this article identifies some complex and emotionally charged tensions that arise in the current practice of natural burial, largely resulting from dissonance with dominant cultural norms. The areas of dissonance explored in this article relate to memorialization in the wild, the naturalness of death itself, and assertions of ecological anthropology.